2014
DOI: 10.4103/1947-2714.136910
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease predicts long-term mortality after major lower extremity amputation

Abstract: Background:Despite low peri-operative mortality after major lower extremity amputation, long-term mortality remains substantial. Metabolic syndrome is increasing in incidence and prevalence at an alarming rate in the USA.Aim:This study was to determine whether metabolic syndrome predicts outcome after major lower extremity amputation.Patients and Methods:A retrospective review of charts between July 2005 and June 2010.Results:Fifty-four patients underwent a total of 60 major lower extremity amputations. Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recently, Assi et al reported that patients with chronic kidney disease have higher risk (OR 2.27; 95% CI 1.02–5.06) of postoperative long-term mortality and concluded that how CKD contributes to worse survival is unclear [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Assi et al reported that patients with chronic kidney disease have higher risk (OR 2.27; 95% CI 1.02–5.06) of postoperative long-term mortality and concluded that how CKD contributes to worse survival is unclear [31]. …”
Section: Discussionmentioning
confidence: 99%